Polymer, preparation method thereof and composition containing polymer
By using a random polymer prepared with a specific proportion of polymer monomers, the problems of high viscosity and poor stability of the positive electrode slurry of lithium batteries are solved, and the slurry viscosity is reduced and the coating speed is improved.
Patent Information
- Application Number
- CN202411407365.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-04-18
AI Technical Summary
The positive electrode slurry of lithium battery has a high viscosity, poor viscosity stability and fluidity, which affects the coating speed.
Using a random polymer, prepared by polymerization reaction from a specific proportion of polymerized monomers, the formed composition has the effect of reducing the viscosity of the slurry and improving stability, thereby increasing the homogenization speed of the slurry and the coating speed of the electrode sheet.
By using the random polymer composition, the viscosity of the slurry is significantly reduced, its stability and fluidity are improved, thereby improving the coating speed and flexibility of the electrode sheet.
Smart Images

Figure BDA0005077020870000081 
Figure BDA0005077020870000111 
Figure BDA0005077020870000121
Abstract
Description
Technical Field
[0001] The present invention specifically relates to a polymer and a preparation method thereof, and a composition containing the polymer. Background Art
[0002] Batteries are key materials in new energy vehicles and renewable energy storage projects. In recent years, the demand for batteries has increased dramatically in both the energy storage field and the new energy electric vehicle field. For battery manufacturers, increasing battery production capacity has become an urgent issue. The increase in battery production capacity can be achieved by increasing the speed of each production process, among which the coating process is the key step to speed up. The high-solid slurry used in coating has a high viscosity and poor fluidity. During the coating process, particles and scratches often appear on the substrate, which greatly affects the output speed of this process.
[0003] Therefore, in order to improve the slurry properties and increase the coating speed of high solid content slurry, the present invention is specially proposed. Summary of the invention
[0004] The technical problem to be solved by the present invention is that the viscosity of the positive electrode slurry of lithium batteries is high, and the viscosity stability and slurry fluidity are poor, which affects the coating speed. The present invention provides a polymer and a preparation method thereof, and a composition containing the polymer. The composition containing the polymer has the characteristics of reducing the slurry viscosity and improving the slurry stability, thereby increasing the slurry homogenization speed, the coating speed of the electrode sheet, and improving the flexibility of the electrode sheet.
[0005] The present invention provides a random polymer, wherein the weight average molecular weight of the random polymer is 20000 g / mol-200000 g / mol;
[0006] The random polymer is obtained by polymerization reaction of the following polymer monomers in mass percentage, wherein the polymer monomers include 5%-35% of a first polymer monomer, 30%-60% of a second polymer monomer and 30%-60% of a third polymer monomer; the mass percentage is the mass percentage of each polymer monomer to the total mass of all polymer monomers;
[0007] The first polymerizable monomer is selected from one or more of acrylic acid, methacrylic acid, itaconic acid and maleic acid;
[0008] The second polymerizable monomer is selected from one or more of 1,3-propylene glycol dimethacrylate, 1,4-butylene glycol dimethacrylate, ethylene glycol dimethacrylate, polyethylene glycol 400 monomethyl ether methacrylate and polypropylene glycol dimethacrylate;
[0009] The third polymerizable monomer is selected from one or more of ethoxylated nonylphenol acrylate, N-vinyl pyrrolidone, N-acryloylmorpholine, benzyl acrylate, benzyl methacrylate, cyclohexyl acrylate and cyclohexyl methacrylate.
[0010] In a preferred embodiment, the first polymerizable monomer is selected from one or more of methacrylic acid, acrylic acid and itaconic acid, such as methacrylic acid, acrylic acid or itaconic acid.
[0011] In a preferred embodiment, the mass percentage of the first polymerized monomer is 5%-25%, for example, 6.5%, 11.27%, 11.36% or 24.24%.
[0012] In a preferred embodiment, the second polymerizable monomer is selected from one or both of ethylene glycol dimethacrylate and polyethylene glycol 400 monomethyl ether methacrylate, for example, ethylene glycol dimethacrylate or polyethylene glycol 400 monomethyl ether methacrylate.
[0013] In a preferred embodiment, the mass percentage of the second polymerizable monomer is 34.09%, 45.45%, 50.7% or 59.74%.
[0014] In a preferred embodiment, the third polymerizable monomer is selected from one or more of N-vinyl pyrrolidone, cyclohexyl acrylate and benzyl methacrylate, such as N-vinyl pyrrolidone, cyclohexyl acrylate or benzyl methacrylate.
[0015] In a preferred embodiment, the mass percentage of the third polymerizable monomer is 30%-55%, for example, 30.3%, 33.76%, 38.03%, 54.54% or 54.55%.
[0016] In a preferred embodiment, the random polymer is obtained by polymerization reaction of the following mass percentages of polymerized monomers, wherein the polymerized monomers are composed of 5%-25% of a first polymerized monomer, 30%-60% of a second polymerized monomer, and 30%-55% of a third polymerized monomer; the mass percentage is the mass percentage of the mass of each polymerized monomer to the total mass of all polymerized monomers;
[0017] The first polymerizable monomer is methacrylic acid, acrylic acid or itaconic acid;
[0018] The second polymerizable monomer is ethylene glycol dimethacrylate or polyethylene glycol 400 monomethyl ether methacrylate;
[0019] The third polymerizable monomer is N-vinyl pyrrolidone, cyclohexyl acrylate or benzyl methacrylate.
[0020] In a preferred embodiment, the weight average molecular weight of the random polymer is 20000 g / mol-80000 g / mol, for example, 22046 g / mol, 27127 g / mol, 26670 g / mol, 37201 g / mol, 42109 g / mol or 68062 g / mol.
[0021] In a preferred embodiment, the polydispersity coefficient of the random polymer is 1.5-3, for example, 1.62, 1.75, 1.77, 1.81, 1.86 or 2.83.
[0022] In a preferred embodiment, the polymerization monomer of the random polymer is selected from the following embodiments 1, 2, 3, 4, 5 or 6:
[0023] Scheme 1: The polymerization monomer is composed of 11.36% methacrylic acid, 34.09% polyethylene glycol 400 monomethyl ether methacrylate and 54.55% N-vinyl pyrrolidone; preferably, the weight average molecular weight of the random polymer is 22046, and the polydispersity coefficient is 1.62;
[0024] Scheme 2: The polymerization monomer is composed of 11.27% methacrylic acid, 50.7% polyethylene glycol 400 monomethyl ether methacrylate and 38.03% N-vinyl pyrrolidone; preferably, the weight average molecular weight of the random polymer is 27127, and the polydispersity coefficient is 1.81;
[0025] Scheme 3: The polymerization monomers are composed of 11.36% methacrylic acid, 34.09% polyethylene glycol 400 monomethyl ether methacrylate and 54.54% N-vinyl pyrrolidone; preferably, the weight average molecular weight of the random polymer is 26670, and the polydispersity coefficient is 1.77;
[0026] Scheme 4: The polymerizable monomers are composed of 11.36% acrylic acid, 34.09% ethylene glycol dimethacrylate and 54.55% N-vinyl pyrrolidone; preferably, the weight average molecular weight of the random polymer is 42109, and the polydispersity coefficient is 1.86;
[0027] Scheme 5: The polymerizable monomers are composed of 24.24% acrylic acid, 45.45% polyethylene glycol 400 monomethyl ether methacrylate and 30.3% cyclohexyl acrylate; preferably, the weight average molecular weight of the random polymer is 37201, and the polydispersity coefficient is 1.75;
[0028] Scheme 6: The polymerization monomer consists of 6.5% itaconic acid, 59.74% polyethylene glycol 400 monomethyl ether methacrylate and 33.76% benzyl methacrylate; preferably, the weight average molecular weight of the random polymer is 68062 and the polydispersity coefficient is 2.83.
[0029] In a preferred embodiment, the polymerization reaction comprises the following steps: in a solvent, in the presence of an initiator, polymerizing the polymerizable monomer to obtain the random polymer.
[0030] The solvent is a conventional solvent for such reactions in the art. In a preferred embodiment, the solvent is a pyrrolidone solvent, such as N-methylpyrrolidone.
[0031] In a preferred embodiment, the solvent is added in three portions, namely, a first solvent, a second solvent and a third solvent; preferably, the polymerizable monomer and the second solvent participate in the polymerization reaction in the form of a polymerizable monomer solution; the initiator and the third solvent participate in the polymerization reaction in the form of an initiator solution; more preferably, the mass of the second solvent accounts for 20%-30% of the total mass of the solvent; the mass of the third solvent accounts for 20%-30% of the total mass of the solvent.
[0032] In a preferred embodiment, the mass ratio of the solvent to the polymerizable monomer is (0.5-5):1, for example (0.8-1.5):1, and for example 1:1.
[0033] The initiator is a conventional initiator for such reactions in the art. In a preferred embodiment, the initiator is selected from one or more of cumene hydroperoxide, tert-butyl hydroperoxide, azobisisobutyronitrile and azobisisoheptanenitrile. Preferably, the initiator is azobisisobutyronitrile.
[0034] In a preferred embodiment, the mass ratio of the initiator to the polymerization monomer is (0.005-0.02):1, for example (0.005-0.015):1, for example 0.006:1, 0.008:1 or 0.012:1.
[0035] In a preferred embodiment, the polymerization reaction temperature is 50-100°C, such as 70-95°C, such as 75°C, 85°C or 90°C.
[0036] In a preferred embodiment, the reaction system of the polymerization reaction consists of the following components: the N-methylpyrrolidone, the polymerization monomer and the azobisisobutyronitrile.
[0037] The progress of the polymerization reaction can be monitored by conventional monitoring methods for such reactions in the art (such as HPLC or TLC), with the disappearance or no-reaction of the polymerization monomers being the endpoint. In a preferred embodiment, the reaction time is 5-10 h, such as 6-8 h, and another example is 6.5 h or 7 h.
[0038] In a preferred embodiment, the polymerization reaction comprises the following steps:
[0039] (1) mixing the first solvent, a portion of the polymerization monomer solution and a portion of the initiator solution, and performing a first stage polymerization reaction to obtain a mixture;
[0040] (2) adding the remaining amount of polymerization monomer solution and initiator solution to the mixture in step (1) to carry out a second stage polymerization reaction to obtain the polymer;
[0041] The mass of the “part of the polymerizable monomer solution” accounts for 10%-30% of the total mass of the polymerizable monomer solution;
[0042] The mass of the “part of the initiator solution” accounts for 10%-30% of the total mass of the initiator solution.
[0043] In a preferred embodiment, the mass of the "part of the polymerization monomer solution" accounts for 20% of the total mass of the polymerization monomer solution; the mass of the "part of the initiator solution" accounts for 20% of the total mass of the initiator solution.
[0044] In a preferred embodiment, the reaction system of the polymerization reaction is composed of the following components: the N-methylpyrrolidone, the polymerization monomer and the azobisisobutyronitrile;
[0045] The polymerizable monomer is the above-mentioned Scheme 1, Scheme 2, Scheme 3, Scheme 4, Scheme 5 or Scheme 6;
[0046] The mass ratio of the N-methylpyrrolidone to the polymerization monomer is (0.8-1.5):1;
[0047] The mass ratio of the azobisisobutyronitrile to the polymerization monomer is (0.005-0.015): 1;
[0048] The polymerization reaction comprises the following steps: (1) mixing the first solvent, a part of the polymerization monomer solution and a part of the initiator solution, and performing a first stage polymerization reaction to obtain a mixture;
[0049] (2) adding the remaining amount of the polymerization monomer solution and the azobisisobutyronitrile solution to the mixture in step (1) to carry out a second stage polymerization reaction to obtain the polymer;
[0050] The mass of the "part of the solution of the polymerized monomers" accounts for 20% of the total mass of the solution of the polymerized monomers; the mass of the "part of the solution of azobisisobutyronitrile" accounts for 20% of the total mass of the solution of azobisisobutyronitrile.
[0051] The present invention provides a method for preparing a random polymer, which comprises the following steps: subjecting the above-mentioned polymerizable monomers to a polymerization reaction to obtain the random polymer; preferably, the operation and conditions of the method for preparing the random polymer are as described above.
[0052] The present invention provides a composition for lithium battery positive electrode slurry, which comprises the random polymer as mentioned above and the solvent as mentioned above.
[0053] In a preferred embodiment, the composition consists of the random polymer and the solvent.
[0054] In a preferred embodiment, the solvent is divided into a first component solvent and a second component solvent, and the second component solvent and the random polymer are used in the form of a polymer solution; the polymer solution is prepared by the following method, in a solvent, in the presence of an initiator, a polymerization reaction is carried out on the polymerizable monomer as described in any of the previous items, and the polymer solution is obtained after the polymerization reaction is completed; the solvent, the initiator, the operation and conditions of the polymerization reaction are as described in any of the present invention.
[0055] In a preferred embodiment, the composition further comprises a long-chain polyether, and the long-chain polyether is selected from one or more of polyethylene glycol, fatty alcohol polyoxyethylene ether, isomeric tridecanol polyoxyethylene ether or lauryl alcohol random polyether; preferably, the long-chain polyether is selected from one or two of polyethylene glycol and isomeric tridecanol polyoxyethylene ether, for example, polyethylene glycol or isomeric tridecanol polyoxyethylene ether.
[0056] In a preferred embodiment, the weight average molecular weight of the polyethylene glycol is 200-600, such as 300-500, and another example is 400.
[0057] In a preferred embodiment, the weight average molecular weight of the isomeric tridecanol polyoxyethylene ether is 500-2000, such as 500-1000, and another example is 750.
[0058] In a preferred embodiment, the mass ratio of the polymer to the long-chain polyether is (0.25-5):1, for example (1-3):1.
[0059] In a preferred embodiment, the solid content of the composition is 45%-70%, such as 45-55%, and for example 50%.
[0060] In a preferred embodiment, the composition consists of the solvent, the polymer and the long-chain polyether, the mass ratio of the polymer to the long-chain polyether is (1-3):1, and the solid content of the composition is 45-55%.
[0061] In a preferred embodiment, the composition consists of the first component solvent, the polymer solution and the long-chain polyether, the mass ratio of the polymer solution to the long-chain polyether is (2-4):1, and the solid content of the composition is 45-55%.
[0062] In a preferred embodiment, the composition is selected from the following embodiments:
[0063] Scheme 1: The composition consists of the polymer solution and N-methylpyrrolidone, and the solid content of the composition is 50%;
[0064] Solution 2: The composition consists of the polymer solution, N-methylpyrrolidone and polyethylene glycol 400, and the solid content of the composition is 50%; the mass ratio of the polymer solution to the polyethylene glycol 400 is 2:1 or 4:1.
[0065] Scheme 3: The composition consists of the polymer solution, N-methylpyrrolidone and isomeric tridecanol polyoxyethylene ether, the solid content of the composition is 50%, and the mass ratio of the polymer solution to the polyethylene glycol 400 is 4:1.
[0066] The present invention provides a lithium battery positive electrode slurry, which comprises the random polymer as described above or the composition as described above.
[0067] In some embodiments, the positive electrode slurry further includes a positive electrode active material and a conductive agent.
[0068] In some embodiments, the positive electrode active material is one or more of lithium iron manganese phosphate, lithium iron phosphate, nickel cobalt manganese ternary material, and nickel cobalt aluminum oxide lithium ternary material; the conductive agent is one or more of conductive carbon black (Super P) or acetylene black.
[0069] In some embodiments, the positive electrode slurry further comprises a binder and an organic solvent; preferably, the binder is polyvinylidene fluoride or polyacrylonitrile, and the organic solvent is N-methylpyrrolidone.
[0070] The present invention provides a lithium battery positive electrode plate, the surface of which is coated with the random polymer or the composition as described above.
[0071] The present invention provides a lithium battery, which comprises the positive electrode sheet as described above.
[0072] Without violating the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0073] The reagents and raw materials used in the present invention are commercially available.
[0074] The positive improvement effect of the present invention is that the polymer of the lithium battery positive electrode slurry of the present invention and the composition containing the polymer have the advantages of reducing the viscosity of the slurry and improving the stability of the slurry, thereby further increasing the slurry homogenization speed, the electrode plate coating speed, and improving the flexibility of the electrode plate. DETAILED DESCRIPTION
[0075] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0076] The sources of polymerization monomers involved in this application are as follows:
[0077]
[0078] The solid content test method in the embodiment of the present application is as follows: 3 groups of parallel samples are taken from the sample to be tested, placed in a 140°C forced air oven, and dried for 3 hours. After cooling, the samples are weighed using a precision balance, and the average solid content is calculated based on the mass of the sample to be tested before and after drying.
[0079] In Examples 1-6, the solid content of the prepared polymer solution is 50-65%.
[0080] Example 1
[0081] 40 g of methacrylic acid, 120 g of polyethylene glycol 400 monomethyl ether methacrylate, 192 g of N-vinyl pyrrolidone and 100 g of N-methyl pyrrolidone were mixed to prepare a mixed monomer solution for later use.
[0082] Mix 2.88 g of azobisisobutyronitrile and 94.88 g of N-methylpyrrolidone to prepare an initiator solution for later use.
[0083] Add 150g of N-methylpyrrolidone to a 1000ml round-bottom four-necked flask, install a stirring paddle, a thermometer, a feeding tube and a condenser, and assemble the reaction device. Turn on the heating device and start stirring.
[0084] When the thermometer in the flask stabilizes and reads 75°C, add the mixed monomer solution and initiator solution into the flask, the mass of the mixed monomer solution added is 20% of the total mass of the mixed monomer solution, the mass of the initiator solution added is 20% of the total mass of the initiator solution, keep warm for 1 hour, then start to dropwise add the remaining mixed monomer solution and initiator solution, the dropping time is 4 hours, then keep warm for 2 hours to obtain a polymer solution.
[0085] The polymer solution was mixed with polyethylene glycol 400 at a mass ratio of 2:1, added into N-methylpyrrolidone, the solid content was adjusted to 50.00%, and stirred evenly to obtain a dispersant for lithium battery positive electrode slurry.
[0086] Example 2
[0087] 40 g of methacrylic acid, 180 g of polyethylene glycol 400 monomethyl ether methacrylate, 135 g of N-vinyl pyrrolidone and 100 g of N-methyl pyrrolidone were mixed to prepare a mixed monomer solution for later use.
[0088] Mix 2 g of azobisisobutyronitrile and 94.88 g of N-methylpyrrolidone to prepare an initiator solution for later use.
[0089] Add 150g of N-methylpyrrolidone to a 1000ml round-bottom four-necked flask, install a stirring paddle, a thermometer, a feeding tube and a condenser, and assemble a reaction device. Turn on the heating device and start stirring. When the thermometer in the flask stabilizes to 85°C, add the mixed monomer solution and the initiator solution to the flask. The mass of the added mixed monomer solution is 10% of the total mass of the mixed monomer solution, and the mass of the added initiator solution is 10% of the total mass of the initiator solution. Keep warm for 1 hour, then start to drop the remaining mixed monomer solution and initiator solution, the dropping time is 5 hours, and then keep warm for 1 hour to obtain a polymer solution.
[0090] The polymer solution was mixed with isomeric tridecanol polyoxyethylene ether in a mass ratio of 4:1, added into N-methylpyrrolidone, the solid content was adjusted to 50.00%, and stirred evenly to obtain a dispersant for lithium battery positive electrode slurry.
[0091] Example 3
[0092] 45.08 g of methacrylic acid, 135.26 g of polyethylene glycol 400 monomethyl ether methacrylate, 216.4 g of N-vinyl pyrrolidone and 100 g of N-methyl pyrrolidone were mixed to prepare a mixed monomer solution for later use.
[0093] Mix 2 g of azobisisobutyronitrile and 94.88 g of N-methylpyrrolidone to prepare an initiator solution for later use.
[0094] Add 150g of N-methylpyrrolidone to a 1000ml round-bottom four-necked flask, install a stirring paddle, a thermometer, a feeding tube and a condenser, and assemble the reaction device. Turn on the heating device and start stirring.
[0095] When the thermometer in the flask stabilizes and reads 90°C, add the mixed monomer solution and initiator solution into the flask, the mass of the mixed monomer solution added is 10% of the total mass of the mixed monomer solution, the mass of the initiator solution added is 10% of the total mass of the initiator solution, keep warm for 0.5h, then start to dropwise add the remaining mixed monomer solution and initiator solution, the dropping time is 5h, then keep warm for 1h to obtain a polymer solution.
[0096] The polymer solution was mixed with polyethylene glycol 400 at a mass ratio of 2:1, added into N-methylpyrrolidone, the solid content was adjusted to 50.00%, and stirred evenly to obtain a dispersant for lithium battery positive electrode slurry.
[0097] Example 4
[0098] 40 g of acrylic acid, 120 g of ethylene glycol dimethacrylate, 192 g of N-vinyl pyrrolidone and 100 g of N-methyl pyrrolidone were mixed to prepare a mixed monomer solution for later use.
[0099] Mix 2.88 g of azobisisobutyronitrile and 94.88 g of N-methylpyrrolidone to prepare an initiator solution for later use.
[0100] Add 150g of N-methylpyrrolidone to a 1000ml round-bottom four-necked flask, install a stirring paddle, a thermometer, a feeding tube and a condenser, and assemble the reaction device. Turn on the heating device and start stirring.
[0101] When the thermometer in the flask stabilizes and reads 75°C, add the mixed monomer solution and initiator solution into the flask, the mass of the mixed monomer solution added is 5% of the total mass of the mixed monomer solution, the mass of the initiator solution added is 5% of the total mass of the initiator solution, keep warm for 0.5h, then start to dropwise add the remaining mixed monomer solution and initiator solution, the dropping time is 4h, then keep warm for 2h to obtain a polymer solution.
[0102] The polymer solution was mixed with polyethylene glycol 400 at a mass ratio of 2:1, added into N-methylpyrrolidone, the solid content was adjusted to 50.00%, and stirred evenly to obtain a dispersant for lithium battery positive electrode slurry.
[0103] Example 5
[0104] 80 g of acrylic acid, 150 g of methoxy polyethylene glycol 400 methacrylate, 100 g of cyclohexyl acrylate and 100 g of N-methylpyrrolidone were mixed to prepare a mixed monomer solution for later use.
[0105] Mix 2.88 g of azobisisobutyronitrile and 94.88 g of N-methylpyrrolidone to prepare an initiator solution for later use.
[0106] Add 150g of N-methylpyrrolidone to a 1000ml round-bottom four-necked flask, install a stirring paddle, a thermometer, a feeding tube and a condenser, and assemble the reaction device. Turn on the heating device and start stirring.
[0107] When the thermometer in the flask stabilizes and reads 75°C, add the mixed monomer solution and initiator solution into the flask, the mass of the mixed monomer solution added is 20% of the total mass of the mixed monomer solution, the mass of the initiator solution added is 20% of the total mass of the initiator solution, keep warm for 1 hour, then start to dropwise add the remaining mixed monomer solution and initiator solution, the dropping time is 4 hours, then keep warm for 2 hours to obtain a polymer solution.
[0108] The polymer solution was mixed with polyethylene glycol 400 at a mass ratio of 2:1, added into N-methylpyrrolidone, the solid content was adjusted to 50.00%, and stirred evenly to obtain a dispersant for lithium battery positive electrode slurry.
[0109] Example 6
[0110] 25 g of itaconic acid, 230 g of polyethylene glycol 400 monomethyl ether methacrylate, 130 g of benzyl methacrylate and 100 g of N-methylpyrrolidone were mixed to prepare a mixed monomer solution for later use.
[0111] Mix 3.42 g of azobisisobutyronitrile and 94.88 g of N-methylpyrrolidone to prepare an initiator solution for later use.
[0112] Add 150g of N-methylpyrrolidone to a 1000ml round-bottom four-necked flask, install a stirring paddle, a thermometer, a feeding tube and a condenser, and assemble the reaction device. Turn on the heating device and start stirring.
[0113] When the thermometer in the flask stabilizes and reads 85°C, add the mixed monomer solution and initiator solution into the flask, the mass of the mixed monomer solution added is 20% of the total mass of the mixed monomer solution, the mass of the initiator solution added is 20% of the total mass of the initiator solution, keep warm for 1 hour, then start to dropwise add the remaining mixed monomer solution and initiator solution, the dropping time is 4 hours, then keep warm for 2 hours to obtain a polymer solution.
[0114] The polymer solution was mixed with polyethylene glycol 400 at a mass ratio of 4:1, added into N-methylpyrrolidone, the solid content was adjusted to 50.00%, and stirred evenly to obtain a dispersant for lithium battery positive electrode slurry.
[0115] Example 7
[0116] The polymer solution and N-methylpyrrolidone were mixed to adjust the solid content to 50%. The polymer solution was the same as that in Example 1, except that the polymer solution was directly used as a dispersant for the positive electrode slurry of the lithium battery without being compounded with the long-chain polyether.
[0117] The GPC molecular weights of the polymers obtained in Examples 1-6 are shown in the following table.
[0118]
[0119]
[0120] Comparative Example 1
[0121] The dispersant for lithium battery positive electrode material slurry is PVP K30 which is commonly used in the market.
[0122] Comparative Example 2
[0123] The intermediate polymer is the same as that in Example 1, except that the polyethylene glycol 400 used in compounding is replaced by polytetramethylene ether 850.
[0124] Effect embodiment 1:
[0125] The following examples illustrate the practical application of the dispersants and preparation methods of Examples 1-6 in the new energy industry. Specifically, a positive electrode slurry for a lithium battery is prepared using N-methylpyrrolidone as a solvent, PVDF (polyvinylidene fluoride) glue as a binder, acetylene black as a conductive agent, and lithium iron phosphate powder as a positive electrode material.
[0126] The positive electrode slurry is composed of: 1. Lithium iron phosphate (brand name Shenghua 10P); 2. SP: Ultra-high density; 3. N-methylpyrrolidone; 4. PVDF (brand name HSV900). All of the above are relatively common materials and brands in this field.
[0127] The dispersants prepared in Examples 1-6 and Comparative Examples 1-3 were added to the slurry in an amount of 0.3% wt. No dispersant was added to the blank sample, and the comparative sample was a commonly used positive electrode slurry dispersant PVP K30. Lithium iron phosphate: PVDF: SP: dispersant = 96.7: 2: 1: 0.3.
[0128] When preparing the positive electrode slurry, first mix and disperse the PVDF glue, dispersant, and N-methylpyrrolidone for 20 minutes, then add lithium iron phosphate and SP and disperse for 70 minutes, and let it stand for defoaming to obtain the positive electrode slurry. The equipment for preparing the slurry is a planetary vacuum degassing mixer. The prepared positive electrode slurry is coated on aluminum foil using a coating method commonly used in the art, and is baked and rolled to form a positive electrode sheet.
[0129] Slurry viscosity is a common testing method in the industry.
[0130] Pole flexibility test: Take the part of the pole piece with uniform thickness, cut it into a long and narrow shape with equal length and width, fold it in half, roll it with a rubber roller 3 times, fold it in half from the crease to the opposite direction, roll it with a rubber roller 3 times. Repeat this process, and when the crease has a breakpoint when viewed against the light, record the number of folds.
[0131] At 25°C, the viscosity of the prepared positive electrode slurry at discharge and after standing for 24 hours, as well as the flexibility of the electrode were tested. The data are shown in Table 1.
[0132] Table 1 Viscosity of positive electrode slurry and flexibility of electrode in each group
[0133]
[0134] It can be seen intuitively from the data in Table 1 that the lithium battery positive electrode dispersant prepared by the present invention has a good effect on the preparation of slurry of lithium iron phosphate powder in a common solvent system (reflected by the slurry discharge viscosity), and this dispersant has a good stabilizing effect on the dispersed positive electrode slurry (reflected by the 24h slurry viscosity), and the storage difficulty of the dispersed slurry is lower than that of PVP K30 commonly used on the market; the lithium battery positive electrode dispersant prepared by the present invention also has a great effect on improving the flexibility of the positive electrode sheet (reflected by the fold of the electrode sheet flexibility test), which is beneficial to the optimization of the preparation process of the battery using this electrode sheet, and is beneficial to improving the energy density of the battery in terms of space utilization.
[0135] Example 7 only uses the polymer prepared by the present invention without compounding with other materials, and the initial viscosity and 24-hour viscosity are not significantly different from those of other examples. Comparative Example 2 uses the polymer prepared by the present invention, but does not use the long-chain polyether defined in the present invention as a compounding material. Although the initial dispersion performance of the positive electrode slurry dispersed in this comparative example is not significantly different from that of the examples, the 24-hour slurry viscosity increases dramatically, and it can be seen that the slurry viscosity stability is poor; in addition, the flexibility of the pole piece is only 2 times.
[0136] The dispersant prepared by the present invention makes the positive electrode slurry dispersed by the dispersant have low viscosity, excellent slurry dispersion effect, good fluidity and good stability. The present invention can be used as a dispersant for lithium battery positive electrode slurry in the preparation of electrode materials.
Claims
1. A random polymer, characterized in that The weight average molecular weight of the random polymer is 20000 g / mol-200000 g / mol; The random polymer is obtained by polymerization reaction of the following polymer monomers in mass percentage, wherein the polymer monomers include 5%-35% of a first polymer monomer, 30%-60% of a second polymer monomer and 30%-60% of a third polymer monomer; the mass percentage is the mass percentage of each polymer monomer to the total mass of all polymer monomers; The first polymerizable monomer is selected from one or more of acrylic acid, methacrylic acid, itaconic acid and maleic acid; The second polymerizable monomer is selected from one or more of 1,3-propylene glycol dimethacrylate, 1,4-butylene glycol dimethacrylate, ethylene glycol dimethacrylate, polyethylene glycol 400 monomethyl ether methacrylate and polypropylene glycol dimethacrylate; The third polymerizable monomer is selected from one or more of ethoxylated nonylphenol acrylate, N-vinyl pyrrolidone, N-acryloylmorpholine, benzyl acrylate, benzyl methacrylate, cyclohexyl acrylate and cyclohexyl methacrylate.
2. The random polymer according to claim 1, characterized in that It meets one or more of the following conditions: (1) the first polymerizable monomer is selected from one or more of methacrylic acid, acrylic acid and itaconic acid, such as methacrylic acid, acrylic acid or itaconic acid; (2) The mass percentage of the first polymerizable monomer is 5% to 25%, for example, 6.5%, 11.27%, 11.36% or 24.24%; (3) the second polymerizable monomer is selected from one or both of ethylene glycol dimethacrylate and polyethylene glycol 400 monomethyl ether methacrylate, for example, ethylene glycol dimethacrylate or polyethylene glycol 400 monomethyl ether methacrylate; (4) the mass percentage of the second polymerizable monomer is 34.09%, 45.45%, 50.7% or 59.74%; (5) the third polymerizable monomer is selected from one or more of N-vinyl pyrrolidone, cyclohexyl acrylate and benzyl methacrylate, such as N-vinyl pyrrolidone, cyclohexyl acrylate or benzyl methacrylate; (6) The mass percentage of the third polymerizable monomer is 30%-55%, for example, 30.3%, 33.76%, 38.03%, 54.54% or 54.55%; (7) The weight average molecular weight of the random polymer is 20000 g / mol-80000 g / mol, for example, 22046 g / mol, 27127 g / mol, 26670 g / mol, 37201 g / mol, 42109 g / mol or 68062 g / mol; (8) The polydispersity coefficient of the random polymer is 1.5-3, for example, 1.62, 1.75, 1.77, 1.81, 1.86 or 2.
83.
3. The random polymer according to claim 1, characterized in that: The random polymer is obtained by polymerization reaction of the following mass percentages of polymerized monomers, wherein the polymerized monomers are composed of 5%-25% of a first polymerized monomer, 30%-60% of a second polymerized monomer, and 30%-55% of a third polymerized monomer; the mass percentage is the mass percentage of the mass of each polymerized monomer to the total mass of all polymerized monomers; The first polymerizable monomer is methacrylic acid, acrylic acid or itaconic acid; The second polymerizable monomer is ethylene glycol dimethacrylate or polyethylene glycol 400 monomethyl ether methacrylate; The third polymerizable monomer is N-vinyl pyrrolidone, cyclohexyl acrylate or benzyl methacrylate; Preferably, the polymerization monomer of the random polymer is selected from the following scheme 1, scheme 2, scheme 3, scheme 4, scheme 5 or scheme 6: Scheme 1: The polymerization monomer is composed of 11.36% methacrylic acid, 34.09% polyethylene glycol 400 monomethyl ether methacrylate and 54.55% N-vinyl pyrrolidone; preferably, the weight average molecular weight of the random polymer is 22046, and the polydispersity coefficient is 1.62; Scheme 2: The polymerization monomer is composed of 11.27% methacrylic acid, 50.7% polyethylene glycol 400 monomethyl ether methacrylate and 38.03% N-vinyl pyrrolidone; preferably, the weight average molecular weight of the random polymer is 27127, and the polydispersity coefficient is 1.81; Scheme 3: The polymerization monomers are composed of 11.36% methacrylic acid, 34.09% polyethylene glycol 400 monomethyl ether methacrylate and 54.54% N-vinyl pyrrolidone; preferably, the weight average molecular weight of the random polymer is 26670, and the polydispersity coefficient is 1.77; Scheme 4: The polymerizable monomers are composed of 11.36% acrylic acid, 34.09% ethylene glycol dimethacrylate and 54.55% N-vinyl pyrrolidone; preferably, the weight average molecular weight of the random polymer is 42109, and the polydispersity coefficient is 1.86; Scheme 5: The polymerizable monomers are composed of 24.24% acrylic acid, 45.45% polyethylene glycol 400 monomethyl ether methacrylate and 30.3% cyclohexyl acrylate; preferably, the weight average molecular weight of the random polymer is 37201, and the polydispersity coefficient is 1.75; Scheme 6: The polymerization monomer consists of 6.5% itaconic acid, 59.74% polyethylene glycol 400 monomethyl ether methacrylate and 33.76% benzyl methacrylate; preferably, the weight average molecular weight of the random polymer is 68062 and the polydispersity coefficient is 2.
83.
4. The random polymer according to any one of claims 1 to 3, characterized in that The polymerization reaction comprises the following steps: in a solvent, in the presence of an initiator, subjecting the polymerization monomer to a polymerization reaction to obtain the random polymer.
5. The random polymer according to claim 4, characterized in that The polymerization reaction satisfies one or more of the following conditions: (1) The solvent is a pyrrolidone solvent, such as N-methylpyrrolidone; (2) The solvent is added in three portions, namely, a first solvent, a second solvent and a third solvent; preferably, the polymerizable monomer and the second solvent participate in the polymerization reaction in the form of a polymerizable monomer solution; the initiator and the third solvent participate in the polymerization reaction in the form of an initiator solution; more preferably, the mass of the second solvent accounts for 20%-30% of the total mass of the solvent; the mass of the third solvent accounts for 20%-30% of the total mass of the solvent; (3) The mass ratio of the solvent to the polymerizable monomer is (0.5-5):1, for example (0.8-1.5):1, and for example 1:1; (4) The initiator is selected from one or more of cumene hydroperoxide, tert-butyl hydroperoxide, azobisisobutyronitrile and azobisisoheptanenitrile. Preferably, the initiator is azobisisobutyronitrile; (5) The mass ratio of the initiator to the polymerization monomer is (0.005-0.02):1, for example (0.005-0.015):1, for example 0.006:1, 0.008:1 or 0.012:1; (6) The polymerization reaction temperature is 50-100°C, such as 70-95°C, such as 75°C, 85°C or 90°C; (7) The reaction system of the polymerization reaction is composed of the following components: the N-methylpyrrolidone, the polymerization monomer and the azobisisobutyronitrile; Preferably, the polymerization reaction comprises the following steps: Step (1): mixing the first solvent, part of the polymerization monomer solution and part of the initiator solution, and performing a first stage polymerization reaction to obtain a mixture; Step (2): adding the remaining amount of polymerization monomer solution and initiator solution to the mixture in step (1) to carry out a second stage polymerization reaction to obtain the polymer; The mass of the "part of the polymerization monomer solution" accounts for 10%-30% of the total mass of the polymerization monomer solution; The mass of the "part of the initiator solution" accounts for 10%-30% of the total mass of the initiator solution; More preferably, the mass of the "part of the polymerization monomer solution" accounts for 20% of the total mass of the polymerization monomer solution; the mass of the "part of the initiator solution" accounts for 20% of the total mass of the initiator solution; Further preferably, the reaction system of the polymerization reaction consists of the following components: the N-methylpyrrolidone, the polymerization monomer and the azobisisobutyronitrile; The polymerizable monomer is the above-mentioned Scheme 1, Scheme 2, Scheme 3, Scheme 4, Scheme 5 or Scheme 6; The mass ratio of the N-methylpyrrolidone to the polymerization monomer is (0.8-1.5):1; The mass ratio of the azobisisobutyronitrile to the polymerization monomer is (0.005-0.015): 1; The polymerization reaction comprises the following steps: Step (1): mixing the first solvent, part of the polymerization monomer solution and part of the initiator solution, and performing a first stage polymerization reaction to obtain a mixture; Step (2): adding the remaining amount of polymerization monomer solution and azobisisobutyronitrile solution to the mixture in step (1) to carry out a second stage polymerization reaction to obtain the polymer; The mass of the "part of the solution of the polymerized monomer" accounts for 20% of the total mass of the solution of the polymerized monomer; the mass of the "part of the solution of azobisisobutyronitrile" accounts for 20% of the total mass of the solution of azobisisobutyronitrile.
6. A method for preparing a random polymer, characterized in that: The method for preparing the random polymer comprises the following steps: subjecting the polymerizable monomer as described in any one of claims 1 to 5 to polymerization reaction to obtain the random polymer; preferably, the operation and conditions of the method for preparing the random polymer are as described in claim 4 or 5.
7. A composition for lithium battery positive electrode slurry, characterized in that: It comprises the random polymer according to any one of claims 1 to 5 and the solvent according to claim 4 or 5.
8. The composition according to claim 7, characterized in that It meets one or more of the following conditions: (1) The composition consists of the random polymer and the solvent; (2) The solvent is divided into a first component solvent and a second component solvent, and the second component solvent and the random polymer are used in the form of a polymer solution; the polymer solution is prepared by the following method: in a solvent, in the presence of an initiator, a polymerization reaction is carried out on the polymerizable monomer as described in any one of claims 1 to 5, and the polymer solution is obtained after the polymerization reaction is completed; preferably, the initiator is as described in claim 5, and the operation and steps of the polymerization reaction are as described in claim 5; (3) The composition further comprises a long-chain polyether, wherein the long-chain polyether is selected from one or more of polyethylene glycol, fatty alcohol polyoxyethylene ether, isomeric tridecanol polyoxyethylene ether or lauryl alcohol random polyether; preferably, the long-chain polyether is selected from one or two of polyethylene glycol and isomeric tridecanol polyoxyethylene ether, such as polyethylene glycol or isomeric tridecanol polyoxyethylene ether; the weight average molecular weight of the polyethylene glycol may be 200-600, such as 300-500, and for example 400; the weight average molecular weight of the isomeric tridecanol polyoxyethylene ether may be 500-2000, such as 500-1000, and for example 750; the mass ratio of the polymer to the long-chain polyether may be (0.25-5):1, such as (1-3):1 (4) The solid content of the composition is 45%-70%, for example 45-55%, for example 50%; Preferably, the composition consists of the solvent, the polymer and the long-chain polyether, and the mass ratio of the polymer to the long-chain polyether is (1-3):1, or the composition consists of the first component solvent, the polymer solution and the long-chain polyether, and the mass ratio of the polymer solution to the long-chain polyether is (2-4):1; More preferably, the composition is selected from the following: Scheme 1: The composition consists of the polymer solution and N-methylpyrrolidone, and the solid content of the composition is 50%; Scheme 2: The composition consists of the polymer solution, N-methylpyrrolidone and polyethylene glycol 400, and the solid content of the composition is 50%; the mass ratio of the polymer solution to the polyethylene glycol 400 is 2:1 or 4:1; Scheme 3: The composition consists of the polymer solution, N-methylpyrrolidone and isomeric tridecanol polyoxyethylene ether, and the solid content of the composition is 50%; the mass ratio of the polymer solution to the polyethylene glycol 400 is 4:
1.
9. A positive electrode slurry for a lithium battery, characterized in that: It comprises a random polymer as described in any one of claims 1 to 5 or a composition as described in 7 or 8; Preferably, the lithium battery positive electrode slurry meets one or more of the following conditions: (1) The positive electrode slurry further comprises a positive electrode active material and a conductive agent; (2) The positive electrode active material is one or more of lithium manganese iron phosphate, lithium iron phosphate, nickel cobalt manganese ternary material, and nickel cobalt aluminum oxide ternary material; the conductive agent is one or more of conductive carbon black (Super P) or acetylene black; (3) The positive electrode slurry further comprises a binder and an organic solvent; preferably, the binder is polyvinylidene fluoride or polyacrylonitrile, and the organic solvent is N-methylpyrrolidone.
10. A lithium battery positive electrode sheet or a lithium battery, characterized in that: The surface of the positive electrode plate is coated with the random polymer as described in any one of claims 1 to 5 or the composition as described in claim 7 or 8; the lithium battery comprises the lithium battery positive electrode plate.